Genetic evidence for auxin involvement in arbuscular mycorrhiza initiation - Hanlon, Meredith T.; Coenen, Catharina (The New phytologist, 2011)
• Formation of arbuscular mycorrhiza (AM) is controlled by a host of small, diffusible signaling molecules, including phytohormones. To test the hypothesis that the plant hormone auxin controls mycorrhiza development, we assessed mycorrhiza formation in two mutants of tomato (Solanum lycopersicum): diageotropica (dgt), an auxin-resistant mutant, and polycotyledon (pct), a mutant with hyperactive polar auxin transport. • Mutant and wild-type (WT) roots were inoculated with spores of the AM fungus Glomus intraradices. Presymbiotic root-fungus interactions were observed in root organ culture (ROC) and internal fungal colonization was quantified both in ROC and in intact seedlings. • In ROC, G. intraradices stimulated presymbiotic root branching in pct but not in dgt roots. pct roots stimulated production of hyphal fans indicative of appressorium formation and were colonized more rapidly than WT roots. By contrast, approaching hyphae reversed direction to grow away from cultured dgt roots and failed to colonize them. In intact seedlings, pct and dgt roots were colonized poorly, but development of hyphae, arbuscules, and vesicles was morphologically normal within roots of both mutants. • We conclude that auxin signaling within host roots is required for the early stages of AM formation, including during presymbiotic signal exchange.